Introduction to superconductivity - Tinkham, Michael (Dover Publications, 2004)
Accessible to graduate students and experimental physicists, this volume emphasizes physical arguments and minimizes theoretical formalism. Topics include the Bardeen-Cooper-Schrieffer and Ginzburg-Landau theories, magnetic properties of classic type II superconductors, the Josephson effect, fluctuation effects in classic superconductors, high-temperature superconductors, and nonequilibrium superconductivity. 109 figures.
Originally published: New York : McGraw-Hill, c1996.
Keywords: Superconductivity.; elektronické knihy; electronic books